The Effect of Arm Muscle Strength, Speed, and Eye-Hand-Foot Coordination on Basketball Dribbling Skills - Vindo Pramata Illanda; Hernawan; Moch. Asmawi; Sujarwo (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study aims to determine the effect of arm muscle strength, speed, and eye-hand-foot coordination on basketball dribbling skills in students participating in basketball extracurricular activities. The research sample was 60 students participating in basketball extracurricular activities at one of the state high schools in jakarta. The research approach used in this study was associative multivariate, with survey methods and test techniques. The analysis technique used the path analysis approach at a significance level of 0.05. The results of the study based on the results of the path analysis test on each hypothesis with the provision of p-value <significance level of 0.05 showed that: there is a direct effect between arm muscle strength on speed, eye-hand-foot coordination, and basketball dribbling skills. There is a direct effect between speed ​​on eye-hand-foot coordination and basketball dribbling skills. There is a direct effect between eye-hand-foot coordination on basketball dribbling skills. There is an indirect effect between arm muscle strength on basketball dribbling skills through eye-hand-foot coordination. There is an indirect effect of speed ​​on basketball dribbling skills through eye-hand-foot coordination. There is an indirect effect of arm muscle strength on basketball dribbling skills through speed. Based on these results, it can be concluded that arm muscle strength, speed, and eye-hand-foot coordination have both direct and indirect effects on the basketball dribbling skills of extracurricular students.